Closed Reduction and Spica Cast Immobilization in Patients Aged 18 Months and Older With Developmental Dysplasia of the Hip - Lei Liu; Qing‐Guang Xiong; Zhen‐Zhen Dai; Jing Ding; Zhen‐Kai Wu; Yun Dai (Orthopaedic Surgery)
ABSTRACT Objectives For children aged 18 months and above with developmental dysplasia of the hip (DDH), treatment typically involves open reduction and hip reconstruction surgery. However, there is limited literature evaluating the efficacy of closed reduction in this patient population. The purpose of this study was to investigate the clinical efficacy of closed reduction and spica cast immobilization treatment for children aged 18 months and above with DDH, as well as the incidence of avascular necrosis of the femoral head (ANFH) and their associated risk factors. Methods We retrospectively reviewed all children aged 18 months and above undergoing closed reduction and spica cast immobilization for DDH in our institution from January 2014 to December 2020. We found 51 hips suffered from closed reduction failure and identified 51 hips with successful closed reduction that matched the hips in the failure group in terms of age (difference < 1 month), weight (difference < 2 kg), and same gender. For patients with bilateral DDH, we prioritized self‐matching, pairing the failed side with the successfully treated side. Relevant clinical data were collected and compared between the two groups. Multiple analyses of risk factors for closed reduction failure and ANFH were conducted by logistic regression. Results In all, 61 patients (102 hips) were included in our study, 2 boys and 59 girls. Compared with the success group, the failure group more commonly had a higher International Hip Dysplasia Institute (IHDI) classification (Type III: 23.53% vs. 15.69%; Type IV: 60.78% vs. 23.53%, p < 0.001), a higher preoperative acetabular index (AI) index (39.42 ± 5.50 vs. 34.03 ± 6.15, p < 0.001), and a higher preoperative migration percentage (MP) (0.81 ± 0.27 vs. 0.54 ± 0.36, p < 0.001). Adjusting for other factors, the IHDI classification Types III–IV was the independent factor associated with closed reduction failure. Compared with the IHDI classification Type I, the failure risk of Type III and Type IV was increased 16.87 and 52.13 times, respectively (p < 0.05). ANFH was observed in three patients (4 hips, 4/102, 3.92%). All cases of ANFH occurred in the closed reduction failure group. The higher preoperative MP was related to the ANFH occurrence significantly through the unilateral factor analysis (0.98 ± 0.05 vs. 0.66 ± 0.34, p < 0.001). Adjusting for other factors, we did not find any independent factor regarding the ANFH occurrence (p > 0.05). Conclusions For patients aged 18 months and above with DDH, an IHDI classification assessment is necessary before closed reduction and spica cast immobilization. For patients classified as IHDI classification Types III and IV, active consideration of open reduction is advisable.